FORECAST OF ANNUAL YIELD OF COCONUTS, BASED ON BIOMIETRICAL CHARACTERS - Jacob Mathew; K. Vijaya Kumar; PTN Nambiar; CH Amarnath (International Coconut Community, 1991)
Based on the observations recorded for four years, at Kasaragod and Kayangulam, Kerala, India, on palms of ordinary tall variety, growing under rainfed conditions, appropriate prediction equations have been proposed to estimate the annual yield of coconuts, at selected periods of the year, based on a total count of nuts in different stages of maturity.